Analysis of expired air with GasCalc: an automated spreadsheet - Egan, D. J. (Sportscience, 1999)
Analysis of expired air collected in bags is the reference standard for determination of oxygen uptake. For aerobic steady-state exercise, it is also possible to determine energy expenditure and substrate utilization. Author presents here an automated Excel spreadsheet for the analyses.